ANALISIS PERAN PEMUDA TERHADAP PEMBANGUNAN PERTANIAN LAHAN PANGAN BERKELANJUTAN DI KABUPATEN LABUHANBATU UTARA - Ritonga, Ajuan; Erlina,; Supriadi, (Jurnal Online Pertanian Tropik, 2019)
The agriculture development of progressive crop land consists of three significant factors such as human resources, natural resources and appropriate technology. The method used in the research is survey, a kind of research of which data is collected from samples over population to represent all population. The type of survey used is explanatory research, a kind of research means to explain the position of variables researched and the relation between a variable and another. The population of the research was all the youths in Labuhan batu Utara being 17-30 years old. According to BPS data in 2013, there were 46,091 youths in Labuhan batu Utara. Sampling used simple sampling random method where sample taken randomly from population based on the probability frequency of all the population’s members. By using the formula of Frank Lynk, it was obtained 96 sample respondents. The conclusion of the research is 1) the youths’ perception to the agriculture development of progressive crop land in Labuhanbatu Utara is positive, 2) the youths’ role to the agriculture development of progressive crop land in Labuhanbatu Utara is positive and 3) the effect of the youths’ role as the agent of change, the agent of development and the agent of modernization is simultaneously significant to the agriculture development of progressive crop land in all the aspects- human resources, natural resources and appropriate technology. Meanwhile the variable of the agent of modernization effects positively but is not significant to the agriculture development of progressive crop land.